Impact of Classroom Lay-out into Proactive Learning - Hernando L. Bernal Jr.; Patrocino C. de Vera II; Jane C. Mangalus (Randwick International of Education and Linguistics Science Journal, 2021)
This study experimented in the use of classroom lay-out, its effectiveness inside the classroom, and its preference for its location. Classroom lay-out involves the learners, their seat locations, and the teacher’s preferences. It used the qualitative inquiry with the phenomenology approach in interpreting the results from the students’ responses. Total enumeration sampling was used where all the students in the Senior high school of Irisan National High School were part of the data gathering respondents. Responses to queries were collected through interviews with the respondents. Results showed that the learners would prefer the teacher to identify where they are to be seated instead of them choosing their own seats. Classroom lay-out might entail an effective strategy to boost the academic performance of a learner, especially in the researcher’s classes in terms of self-assessment and showing of authority. However the learners think of assessing themselves in terms of their seat location and the classroom lay-out, they still see the teacher as the one in authority in leading the effectiveness of the classroom lay-out.